Asymmetric distributions in pressure/load fluctuation levels during blade-vortex interactions. (January 2017) - Peng, Di; Gregory, James W.
Abstract: The separation distance ( h / c ) between vortex and blade is a critical parameter in blade-vortex interaction, which strongly affects the magnitudes of induced pressure fluctuations (peak-to-peak values) and noise on helicopters. Parallel blade-vortex interaction (BVI) was studied in a subsonic wind tunnel to better understand the flow physics of BVIs with small h / c values and further improve the current BVI alleviation schemes. A vortex was generated by a sudden pitch motion applied to an airfoil through a pneumatic system. As the vortex interacted with a downstream target airfoil in a parallel manner, the vortex dynamics and induced loads were studied. The induced pressure/load fluctuations were obtained from the unsteady pressure data on the target airfoil, and the flow fields during the interaction were visualized using particle image velocimetry (PIV). Despite the fact that a symmetric airfoil was studied, the pressure data clearly displayed an asymmetric distribution in fluctuation levels above and below the chord line ( h / c =0). Maximum pressure and load fluctuations occurred when the vortex passed on one side of the symmetric airfoil with small h / c, rather than in the head-on case ( h / c =0). This side of the airfoil is defined as the strong fluctuation side, with the opposite side defined as the weak fluctuation side. PIV data revealed that this phenomenon was directly related to the asymmetry in velocity field induced by the vortex. The load fluctuation level also exhibited weak dependence on the decay in vortex strength due to both viscous- and inviscid-type interaction with the airfoil. However, the role of vortex decay became insignificant at higher Reynolds number due to lower decay rate. These findings cleared some confusion in previous studies and suggested that the magnitude of BVI fluctuations could be reduced by passing the airfoil below a clockwise vortex or above a counter-clockwise vortex.